Unraveling the Spiraling Radiation: A Phylogenomic Analysis of Neotropical Costus L - Valderrama, Eugenio; Sass, Chodon; Pinilla-Vargas, Maria; Skinner, David; Maas, Paul J. M.; Maas-van de Kamer, Hiltje; Landis, Jacob B.; Guan, Clarice J.; Specht, Chelsea D. (Frontiers in Plant Science, 2020)
The family of pantropical spiral gingers (Costaceae Nakai; c. 125 spp.) can be used as a model to enhance our understanding of the mechanisms underlying Neotropical diversity. Costaceae has higher taxonomic diversity in South and Central America (c. 72 Neotropical species, c. 30 African, c. 23 Southeast Asian), particularly due to a radiation of Neotropical species of the genus Costus L. (c. 57 spp.). However, a well-supported phylogeny of the Neotropical spiral gingers including thorough sampling of proposed species encompassing their full morphologic and geographic variation is lacking, partly due to poor resolution recovered in previous analyses using a small sampling of loci. Here we use a phylogenomic approach to estimate the phylogeny of a sample of Neotropical Costus species using a targeted enrichment approach. Baits were designed to capture conserved elements’ variable at the species level using available genomic sequences of Costus species and relatives. We obtained 832 loci (generating 791,954 aligned base pairs and 31,142 parsimony informative sites) for samples that encompassed the geographical and/or morphological diversity of some recognized species. Higher support values that improve the results of previous studies were obtained when including all the available loci, even those producing unresolved gene trees and having a low proportion of variable sites. Concatenation and coalescent-based species trees methods converge in almost the same topology suggesting a robust estimation of the relationships, even under the high levels of gene tree conflict presented here. The bait set design here presented made inferring a robust phylogeny to test taxonomic hypotheses possible and will improve our understanding of the origins of the charismatic diversity of the Neotropical spiral gingers.